Research progress on branched-chain amino acid aminotransferases - Chen, Can; Naveed, Hassan; Chen, Keping (Frontiers in Genetics, 2023)
Branched-chain amino acid aminotransferases, widely present in natural organisms, catalyze bidirectional amino transfer between branched-chain amino acids and branched-chain α-ketoacids in cells. Branched-chain amino acid aminotransferases play an important role in the metabolism of branched-chain amino acids . In this paper, the interspecific evolution and biological characteristics of branched-chain amino acid aminotransferases are introduced, the related research of branched-chain amino acid aminotransferases in animals, plants, microorganisms and humans is summarized and the molecular mechanism of branchedchain amino acid aminotransferase is analyzed. It has been found that branchedchain amino acid metabolism disorders are closely related to various diseases in humans and animals and plants, such as diabetes, cardiovascular diseases, brain diseases, neurological diseases and cancer. In particular, branched-chain amino acid aminotransferases play an important role in the development of various tumors. Branched-chain amino acid aminotransferases have been used as potential targets for various cancers. This article reviews the research on branched-chain amino acid aminotransferases, aiming to provide a reference for clinical research on targeted therapy for various diseases and different cancers.